Structure of movement of a turning technique used in the event of special techniques in Taekwon-do ITF - Wasik, J. (Archives of Budo, 2009)
One of the kicks performed in the event of special techniques in Taekwon-do ITF is the flying reverse turning kick (according to the Taekwon-do terminology: Twimyo bandae dollyo chagi). To make a competitor kick in the best way, it is necessary to know all the elements responsible for a good kick, in order to get the best sports result. Twimyo bandae dollyo chagi is a difficult movement that requires a lot of physical fitness. When you start to learn a technique, you have to know what the movement looks like, what the position of the body is and what factors influence the movement. The aim of this work was to describe the structure of the movement during a flight reverse turning kick (in Taekwon-do terminology: Twimyo bandae dollyo chagi). A 17-year-old competitor weighing 75 kg and measuring 179 cm with the International Championship Class was analyzed. He performed a flight reverse turning kick. With the use of the BTS Smart system, data about the relocation and speed of characteristic point of the competitor`s body was obtained. Parameters which describe the spatial and time structure of the movement were analyzed. The conclusion from the research is that the height of the jump depends on four basic elements: the height of the centre of gravity at the moment of jumping, the height of jumping of the COG, the height of flying of the COG and the height of rising the kicking leg. The height of the COG depends on somatic features and the position of the body. The height of the jump is a function of motoric features. The bigger the Y component of the speed of jumping and change of vertical speed (which is influenced by the force of jumping and the rotational movement of the legs and torso), the higher the height of flying of COG. The height of rising the kicking leg depends on the angle speed and the position of the body when the kick is performed.